The Metaverse: The Essence, Research Streams, and Potential Applications in Marketing - Marcin Awdziej; Dagmara Plata-Alf; Jolanta Tkaczyk (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: The objective of this article is to identify the main research streams and research gaps relating to the metaverse in management sciences, particularly in the field of marketing.